Pengaruh Persepsi Siswa Tentang Layanan Penguasaan Konten Terhadap Prokrastinasi Akademik - puspita, relegia ita (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The study is based on the phenomenon on the ground when researchers conducted a preliminary study at the time of PPL in SMA 3 Semarang, which shows that the relatively high level of academic procrastination. The purpose of this study is to predict the positive influence between students' perceptions about the mastery of content services to academic procrastination . This type of research is ex-post facto study. The study population was all students SMA 3 Semarang totaling 1008 students and the sample totaled 204 students use simpe random sampling by a draw. Data collection method used is a psychological scale and questionnaire questionnaire. The instrument has been tested for use in research the validity of the formula used by the Pearson product moment and reliability of the instrument with Alpha formula. Data were analyzed using simple regression analysis. The results showed a 43% positive influence on students' perceptions about the mastery of content services to academic procrastination. Conclusions from this research that there is a positive influence on students' perceptions about the mastery of content services to academic procrastination.